Application of mechanisms of public-private partnership in the agro-industrial complex - Nurseitov, A.A.; Adilbekova, B.S.; Abilkassym, B.E. (BUKETOV BUSINESS REVIEW, 2017)
The paper explored the methodologies relating to the use of the public-private partnership (PPP) mechanisms in Kazakhstan’s agribusiness. The research has been motivated by the strong need on using the PPPs in agribusiness. The analyses carried out under this study revealed the typology and categorization of agro-PPP projects. The primary goal of those projects has been found to target the revitalization of the dynamics in the development of Kazakhstan’s agribusiness. The paper explored diverse methodologies through the prism of their relevancy for Kazakhstan’s agro-PPPs. As the outcomes of the study, it has outlined the project assessment techniques that may be applied in evaluating the agro-PPP projects. Although the focus of the paper has mainly been on Kazakhstan, other countries will have also benefited from the findings of the paper. Likewise, the findings of the research may be useful for broad users, including the agro-PPP entities, central and regional public authorities, who are involved in decision making, and project managers.